Is it Justified to Include Urine Cultures in Early (< 72 Hours) Neonatal Sepsis Evaluations of Term and Late Preterm Infants? - Riskin, Arieh; Toropine, Arina; Bader, David; Hemo, Miri; Srugo, Isaac; Kugelman, Amir (American Journal of Perinatology, 2013)
Objective Evaluate the need for urine culture in early neonatal sepsis workup of term and late preterm infants.Study Design Urine culture by suprapubic aspiration or catheter was included in early sepsis evaluations of 173 term and late preterm newborns (mean gestational age 38.6 ± 2.0 weeks) during a 6-month study period. A historic control group included 182 newborns (38.6 ± 2.9 weeks) who had sepsis evaluations without routine urine cultures a year earlier.Results Urine cultures were sampled in 106 (61%) of the study group, No significant differences were found between study and control groups in the rate of bacteremia (1.73% versus 2.2%) or urinary tract infection (UTI; 0.94% versus 1.1%), which was low. Early UTIs were not accompanied by bacteremia or structural anomalies and were associated with exacerbation of neonatal jaundice in two of three infants.Conclusions There seems to be no justification for routine urine culture in early neonatal sepsis workup of term and late preterm infants, unless there are accompanying clinical symptoms, usually related to neonatal jaundice.
Keywords: neonates; early neonatal sepsis; urinary tract infection (UTI); urine culture